Forecasting, valuation and portfolio returns of stock market evolution: problems, paradoxes and efficient information. Worldwide implications and Romanian evidence - Turcaș, Florin; Dumiter, Florin Cornel; Brezeanu, Petre; Boiță, Marius (Journal of Business Economics and Management, 2020)
The purpose of this paper is to make a quantitative and qualitative critical analyse regarding the three important aspects of stock market evolution. First, the forecasting problems are presented and analyse in order to establish the main problems and the potential solutions. Second, the valuation problems are tackled in order to observe different trends and directions of solving these issues. Third, the portfolio return forecasts are mandatory in order to establish the results of the titles/market evolutions. The methods used in our research reveal the importance of adopting some important econometric tools in order to test the robustness of different main theories of the stock market and some important practices used among investors. The scope of the research was to give a quid pro quo in order to confer potential solutions regarding problems, paradoxes and efficient information of the stock market. The empirical results reveal that besides the critical side of the theories this paper sets a basis for a new eclectic approach regarding the probabilities that a title achieves certain values within a reasonable time frame. The main conclusion of this article suggests’ that the current theories register some gaps regarding the adherence into stock markets’ realities.First published online 16 December 2019